Dietary laminarin administration to enhance the immune responses, promote growing and strengthen physique in Ictalurus punctatus. (18th March 2021) - Jiang, Hucheng; Wang, Minghua; Zheng, You; Chen, Fengwei; Fu, Longlong; Zhong, Liqiang; Chen, Xiaohui; Bian, Wenji
Abstract: In this study, the different dosage of laminarin groups (normal fodder group (Control), normal fodder add 1 g laminarin group (AL1), normal fodder add 2 g laminarin group (AL2), normal fodder add 4 g laminarin group (AL4) and normal fodder add 8 g laminarin group (AL8)) were set. After 45 days, the growth, enzyme activity and immune‐related gene were measured to assess the effect of feeding laminarin on Ictalurus punctatus . Laminarin (4 g dosage) can significantly increase body length ( p  < .05) and BMI (body mass index) value in 8 g dosage group ( p  < .05). Lysozyme, acid phosphatase, aspartate aminotransferase, catalase, superoxide dismutase, pepsin, amylase and trypsin activity are increased with the dosage of laminarin increasing, and have a significant difference at the dosage of 4 g and 8 g group ( p  < .001). However, the serum cortisol content, alkaline phosphatase and lipase activity have a significant inhibition in high‐dosage groups ( p  < .001). The expression of TLR5 gene in group of 4 g dosage was significantly upregulated ( p  < .05). The expression of SOCs gene in groups of 2 g ( p  < .05), 4 g ( p  < .001) and 8 g ( p  < .001) dosage was significantly downregulated. The expression of IGF2 and STAT5 genes was significantly upregulated in high‐dosage laminarin groups. Generally, larminarin enhances the immune response, reduces the rate of energy decomposition required and improves food absorption. This shows that the larminarin improves the physical quality and increases productivity of I . punctatus, and offers great potential for application in the aquaculture industry.